125I Seeds Radiation Induces Paraptosis-Like Cell Death via PI3K/AKT Signaling Pathway in HCT116 Cells. (19th December 2016) - Hu, Lelin; Wang, Hao; Zhao, Yong; Wang, Junjie
Abstract : 125 I seeds brachytherapy implantation has been extensively performed in unresectable and rerecurrent rectal carcinoma. Many studies on the cancer-killing activity of 125 I seeds radiation mainly focused on its ability to trigger apoptosis, which is the most well-known and dominant type of cell death induced by radiation. However our results showed some unique morphological features such as cell swelling, cytoplasmic vacuolation, and plasma membrane integrity, which is obviously different to apoptosis. In this study, clonogenic proliferation was carried out to assay survival fraction. Transmission electron microscopy was used to analyze ultrastructural and evaluate morphologic feature of HCT116 cells after exposure to 125 I seeds radiation. Immunofluorescence analysis was used to detect the origin of cytoplasmic vacuoles. Flow cytometry analysis was employed to detect the size and granularity of HCT116 cells. Western blot was performed to measure the protein level of AIP1, caspase-3, AKT, p-Akt (Thr308), p-Akt (Ser473), and β -actin. We found that 125 I seeds radiation activated PI3K/AKT signaling pathway and could trigger paraptosis-like cell death. Moreover, inhibitor of PI3K/AKT signaling pathway could inhibit paraptosis-like cell death induced by 125 I seeds radiation. Our data suggest that 125 I seeds radiation can induce paraptosis-like cell death via PI3K/AKT signaling pathway.